Analisis Penagihan Pajak dengan Surat Teguran dan Surat Paksa terhadap Penerimaan Pajak pada Kantor Pelayanan Pajak Pratama Jatinegara Jakarta Timur - Budi Tri Rahardjo, Ak., M.Ak., CA; Rosmawati rosma (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aims to analyze warning letter reports and tax strengths and revenues from 2010-2014 KPP Pratama Jatinegara. The analysis used is descriptive analysis using the effectiveness of warning and forced letters and the ratio of income tax arrears. Data is collected through study of literature and articles. The results showed that tax disbursement with a warning letter and a letter of power in Jatinegara Primary KPP in general could be classified as ineffective either because a number of sheets or nominal values mentioned in the warning letter and forced letters did not reach 100%. Besides that, the taxpayer does not submit the SPT, SKPKB, SKPKBT etc., taxpayers in taxes do not recognize that there is a tax debt, taxpayers cannot settle the amount of debt, taxpayers submit requests for installment payments because financial conditions are not possible if they have to paid in total, taxpayers file objections to the amount of tax arrears, and taxpayers neglect it. The awareness of taxpayers in the tax payment of forced letter tax arrears, the lack of an active role of the forced letter tax arrears, and cannot be contacted because the taxpayer changes the address and does not report to the tax office.